PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS IV SD NEGERI I BANPRES - Irma Erfiana; Eka Lokaria; Dedy Firduansyah (Jurnal Perspektif Pendidikan, 2022)
This study aims to determine the completeness of student learning outcomes after applying the Make A Match Learning Model in Social Studies subjects for fourth grade students of SD Negeri 1 Banpres. This type of research is quantitative research and the research method used is quasi-experimental research using pre-test and post-test research designs. Using multiple choice questions totaling 14 questions. The research sample is a class, namely class IV A consisting of 28 students and. The data analysis technique used the following steps: normality test, Z test. The average pre-test score was 47.70 and the post-test average was 85.20. Based on the results of the z-test analysis, the value of Zhitung (8.58) and Ztable 1.64 if compared, then Zhitung > Ztable. For the final test at a significant level of 0.05, it can be concluded that the social studies learning outcomes of Grade IV students at SD Negeri 1 Banpres after the Make A Match Learning Model were significantly completed.